A Coherent Strategy for a Changing Region?: The Obama Administration Foreign Policy and the "Arab Spring" - Tovar Ruiz, Juan (UNISCI Discussion Papers, 2015)
The Foreign Policy of the Obama Administration has been clearly affected by the process of change in the Middle East known as Arab Spring. The debate about the nature of the Strategy of the president for that region has been added to the previous debate about the mere existence of an Obama doctrine, as the region has turned to be the main battlefield of the ideological groups of the American Foreign Policy: realists, neoconservatives and liberal interventionists. The need of balancing the strategic and security interest with the promotion of values such as the liberal democracy or the human rights has been followed by some kind of return to a realist strategy, of limited intervention, founded in core strategic interests and different solutions for different contexts. The contemporary conflict in states like Iraq or Syria, presents enormous uncertainties which should be confronted in the short term.
Keywords: Foreign Policy; Arab Spring; doctrine; ideology; democracy; strategic interests.